Automotive Nuance Textbook; English Learning Materials for Automotive Engineering Vocational Students - St. Rismawati Nasir; Rustan Santaria; Sukirman; Yulia Savhika (Institut Agama Islam Negeri Palopo, 2025)
English teaching materials for vocational students in automotive engineering classes often fail to meet contextual needs, hindering effective learning. This research uses the ADDIE model to develop a tailored Automotive Nuance Textbook; English Learning Materials For Automotive Engineering Vocational Students using the Research and Development approach. The study involved 25 students chosen randomly, focusing on needs analysis, design, development, implementation, and evaluation stages. Based on the needs analysis instrument results, the English material packaged in automotive nuance textbook for vocational students if developed will be very useful because it is designed according to the needs of the Automotive Engineering Vocational Students. then from the results of the instrument effectiveness test and the final analysis of automotive students, it was found that each percentage had a score in the 100% category. Results indicated a strong need for specialized English materials, showing high effectiveness in addressing students' learning needs. Keywords: Automotive Nuance Textbook; English Learning; English Material; Vocational Students